Hunter‐gatherer studies and human evolution: A very selective review. Issue 4 (25th March 2018) - Hawkes, Kristen; O'Connell, James; Blurton Jones, Nicholas
Abstract: The century long publication of this journal overlapped major changes in the sciences it covers. We have been eyewitnesses to vast changes during the final third of the last century and beginning of this one, momentous enough to fundamentally alter our work separately and collectively. One (NBJ) from animal ethology, another from western North American archaeology (JOC), and a third (KH) from cultural anthropology came to longtime collaboration as evolutionary ecologists with shared focus on studying modern hunter‐gatherers to guide hypotheses about human evolution. Our findings have radically revised hypotheses each of us took for granted when we began. Our (provisional) conclusions are not the consensus among hunter‐gatherer specialists; but grateful that personal reflections are invited, we aim to explain how and why we continue to bet on them.